ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA DENGAN MENGGUNAKAN PROSEDUR POLYA - Nadhira Syahla Kamila; Alpha Galih Adirakasiwi (IKIP Siliwangi, 2021)
This research aims to analyze the types of errors caused by students in solving math story problems based on Polya's completion steps. This research used a descriptive research method with a qualitative approach and the research subjects were 22 students of class 10. The data collection technique used was a description test with 3 items. The results showed that the student's errors at the step of understanding the problem were 32.46% with a fairly high category, the student's errors at the step of making a plan were 12.93% with a small category, the student's errors at the step of carrying out the plan were 25.19% with a high enough category, and the student’s errors at the step of look back at the completed solution were of 29.43% with a high enough category.